PHYSICO-CHEMICAL OF POLYANIONIC CELLULOSE (PAC-R) POLYMER ON BONDING ABILITY IN THE CEMENTING MATERIAL USED FOR OIL AND GAS WELL - Kuvanchbay, Bekzat; Tolegen, Bektas (School of Mining and Geosciences, 2023)
The ability of the cement sheath to bond effectively with the casing or formation depends on its tensile strength and Young's modulus, which determine its ability to withstand deformation under load without separating. The aim of this research was to explore the impact of the concentration of PAC-R copolymer and the duration of curing on the bonding capacity of the cementing substance utilized in oil and gas wells. The study carried out two sets of experiments to assess the chemical and mechanical features of the cement specimens. The compressive strength of the samples was measured after curing for 1 day and 3 days at 80 ℃ in an OFITE curing chamber. The uniaxial test results showed that samples with 10% and 20% PAC-R copolymer concentrations had significantly lower axial loads and axial stresses compared to control samples. As the amount of polymer was raised from 10% to 20%, the compressive strength also went up. This happened because the polymer was able to fill in tiny cracks and gaps in the cement, making the matrix more uniform and compact. As a result, it became more resistant to being compressed. The reduction in the Young modulus was particularly noticeable when using a 10% PAC-R copolymer concentration. As the polymer concentration increased from 10% to 20%, the Young modulus values displayed an inclination to rise.
Keywords: Type of access: Open Access; Polyanionic cellulose (PAC-R) polymer